Detection of enteroviruses from water samples using optimised RT-PCR with universal primers. (23rd June 2009) - Zhang, C.M.; Liu, Y.J.; Wang, X.C.; Xue, X.P.
A method for rapid detection of enteroviruses in water sample was established by using RT-PCR with universal primers with PV1, PV2, PV3 and CVB3 as the reference viruses. The conditions for simultaneous detection of different enteroviruses were experimentally determined and the detection limit of virus was found to be 38CCID50. Virus concentration, RNA extraction and RT-PCR operation were the main factors affecting the sensitivity of virus detection. By applying the procedures to water samples with seeded PV1 viruses, the interference of impurities in practical waters on enteroviruses detection was investigated. The method was proved to be suitable for practical application.